Agency and political mobilization of human and non-human beings in the Mazateca region, Mexico: the visible, the legitimate and the legible - PIÑA ALCÁNTARA, Sarai; VALDÉS BIZE, Federico (Utopía y Praxis Latinoamericana, 2024)
This research seeks to reflect on collective action beyond the human, opening the concept towards other beings and worlds, from political ontology perspective and rooted in ethnographic practice. The method used is that of a reflective dialogue about our ethnographies, based on an engagement with social theory and the development of our political positions. Our fieldwork began in 2005 and 2009, with prolonged stays up to the present, mainly in the municipalities of Huautla de Jiménez and San José Tenango. The result has been: One, our transformation and decentering, by making visible the political relations that involve non-human and extra-human beings, in order to account for other polities and relationships. Two, to question our anthropological work towards an horizontal dialogue between science and other epistemes emanating from indigenous peoples. Three, that anthropology can help the quest of a better living, questioning its colonial heritage, and reflecting on the pretension of academic neutrality in contexts of dispossession and death in the indigenous territories.